DNA Quality Testing of Isolated Stored Giemsa Blood Smear Samples using Geneius™ Micro gDNA Extraction Kit as An Alternative Sample for Malaria Molecular Examination - Dewi Saroh; Dwi Haryatmi; Rendyansah Agung Widodo (Indonesian Journal of Global Health Research, 2025)
The gold standard for malaria examination is microscopic examination. However, microscopic examination has many shortcomings, namely the difficulty of distinguishing between Plasmodium sp. species when mixed infections occur. Other malaria examinations for screening can be done with RDT. However, it also has shortcomings, namely the minimum number of parasites that can be detected is 100 parasites/ul. Molecular examination is the most sensitive and accurate examination in the diagnosis of malaria. The initial stage of molecular examination is the DNA isolation stage. This DNA isolation is very important in determining the success of molecular examination. Isolation of Plasmodium sp. DNA using blood smear samples is still rarely done and there is no standard procedure for isolating DNA from blood smears. The purpose of this study was to determine whether stored Giemsa blood smears can be used as samples in DNA isolation in malaria cases. The method used in isolation is using the Geneius™ Micro gDNA Kit. The results of the study were that stored Giemsa blood smear samples of Plasmodium vivax for 3 months could be isolated using the Geneius™ Micro gDNA Kit and could be used as DNA templates for amplification with target gene primers.